Champa chatti jamaat ke liye - Farooqui, Fouzia Ahsan (Oxford university press, Karachi., 2023)
Champa for Class 6 is an engaging Urdu textbook by Oxford University Press, designed to develop language skills through stories, poems, and exercises. It emphasizes reading comprehension, creative writing, and grammar, while fostering an appreciation for Urdu literature and cultural values. The book combines literary and practical language activities to enhance students' linguistic proficiency.
Keywords: Urdu